Antibacterial Activity of Chloroform Extract from Tagetes Erecta L. Flowers - Zainab Aziz Ali; Thamer M. Jasim; Widad M K Alani (College of Pharmacy / Mustansiriyah University, 2019)
Antibacterial activity of chloroform of T. erecta   flower extract was performed on six-gram negative bacteria species (Serratia marcescens, Acinobacter Spp., Escherichia coli, Salmonella Spp., Morganella morganii, Pseudomonas aeruginosa) and two-gram positive Bac-   teria (Streptococcus pneumonia and Staphylococcus aureus). The antibacterial study was performed by ager well diffusion and disk diffusion methods. The extract shows good results against examined bacteria and the results obtained by agar well diffusion method was better than those obtained from disk diffusion method.